Virtual Modeling of Postoperative Alignment After Adult Spinal Deformity Surgery Helps Predict Associations Between Compensatory Spinopelvic Alignment Changes, Overcorrection, and Proximal Junctional Kyphosis. Issue 19 (1st October 2017) - Lafage, Renaud; Bess, Shay; Glassman, Steve; Ames, Christopher; Burton, Douglas; Hart, Robert; Kim, Han J.; Klineberg, Eric; Henry, Jensen; Line, Breton; Scheer, Justin; Protopsaltis, Themistocles; et al.
Abstract : Study Design: Retrospective review of a prospective multicenter database. Objective: To develop a method to analyze sagittal alignment, free of the influence of proximal junctional kyphosis (PJK), and then compare PJK to non-PJK patients using this method. Summary of Background Data: PJK after adult spinal deformity (ASD) surgery remains problematic as it alters sagittal alignment. The present study proposes a novel virtual modeling technique that attempts to eliminate the confounding effects of PJK on postoperative spinal alignment. Methods: A virtual spinal modeling technique was developed on a retrospective ASD cohort of patients with multilevel spinal fusions to the pelvis with at least 2-year postoperative follow-up. The virtual postoperative alignment (VIRTUAL) was created from the postoperative alignment of the instrumented segments and the preoperative alignment of the unfused segments. VIRTUAL was validated by comparisons to actual 2-year postoperative alignment (REAL) in non-PJK patients. Patients were then divided into two groups: PJK and non-PJK based on the presence/absence of PJK at 2 years postoperatively. PJK and non-PJK patients were compared using VIRTUAL and REAL. Results: A total of 458 patients (78F, mean 57.9 yr) were analyzed. The validation of VIRTUAL versus REAL demonstrated correlation coefficients greater than 0.7 for all measures except sagittal vertical axis (SVA; r  = 0.604). At 2 years, REAL alignment in PJK patients demonstrated a smaller pelvic incidence minus lumbar lordosis and a larger thoracic kyphosis than non-PJK patients, but similar SVA, T1 pelvic angle, and pelvic tilt. An analysis of VIRTUAL demonstrated that patients with PJK had a smaller pelvic incidence minus lumbar lordosis, pelvic tilt, SVA, and T1 pelvic angle than non-PJK patients ( P  < 0.05). Conclusion: This technique demonstrated strong correlations with actual postoperative alignment. Comparisons between REAL and VIRTUAL alignments revealed that postoperative PJK may develop partially as a compensatory mechanism to the overcorrection of sagittal deformities. Future research will evaluate the appropriate thresholds for deformity correction according to age and ASD severity. Level of Evidence: 3